Europe’s stratified social space: diagnosis and remedies - Anheier, Helmut K.; Falkenhain, Mariella (Global policy, 2013)
For some 60 years now, various measures have been introduced to bring Europeans together as citizens, based on the idea that increased cross-border encounters would create familiarity, generate a sense of community, facilitate economic activities and ultimately bring about a shared identity, however fragile at first. Town twinning and numerous exchange and mobility programmes of many kinds are cases in point. These programmes typically were anchored in the municipal, educational and vocational realms. While these mechanisms functioned well, some seem to be losing their innovative capacity; yet all reveal a structural middle-class bias. On the whole they systematically exclude those groups among which the rise of Euro-scepticism and support for anti-European political parties is the strongest, particularly the less well-educated and the new precariat. With the fiscal crises reducing the capacity of many EU member states to support the European Project financially, what mechanisms or policy instruments could, in the sense of social engineering, strengthen social bonds across borders and re-energise Europe’s social space? Policy Implications • Mobility programmes for tertiary education and vocational training regularly do not reach lower social status groups. They should be made more inclusive by using targeted recruitment campaigns and monetary incentives. • Teachers, social workers in youth organisations, community activists or coaches in sports clubs can be effective in reaching out to youths. The success of EU mobility programmes is dependent on such social mediators. Professions and institutions with high social outreach should themselves become targets of training and exchange programmes. • Town twinning has become overly institutionalised, relying heavily on established professional and local elites. Town twinning projects need to open up socially and involve a greater variety of participants, in terms of social class, ethnic background and age. • Europe needs to embark on an ambitious and large-scale volunteer programme. Such a programme should be incentivised to include participants of the new precariat, be linked to qualification schemes and become part of a sustained campaign to help ‘build Europe from below’.